Proceedings. The IEEE 5th International Conference on Intelligent Transportation Systems
DOI: 10.1109/itsc.2002.1041322
|View full text |Cite
|
Sign up to set email alerts
|

A statistical model of vehicle emissions and fuel consumption

Abstract: Abstract-Many vehicle emission models are overly simple, such as the speed dependent models used widely, and other models are sufficiently complicated as to require excessive inputs and calculations, which can slow down computational time. We develop and implement an instantaneous statistical model of emissions (CO 2 , CO, HC, and NOx) and fuel consumption for light-duty vehicles, which is simplified from the physical loadbased approaches that are gaining in popularity. The model is calibrated for a set of veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
4

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 5 publications
1
124
0
4
Order By: Relevance
“…The "second by second" data was input into the regression process, some transformations were applied to the variables in order to have a greater set of independent variables in the model. In previous studies [8,10] a combination of speed and acceleration raised to different power showed to be a good approach for this type of regressions. Speed and acceleration were raised to the square and cubic power and combined with each other.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The "second by second" data was input into the regression process, some transformations were applied to the variables in order to have a greater set of independent variables in the model. In previous studies [8,10] a combination of speed and acceleration raised to different power showed to be a good approach for this type of regressions. Speed and acceleration were raised to the square and cubic power and combined with each other.…”
Section: Resultsmentioning
confidence: 98%
“…The inclusion of instantaneous variables, such as speed and acceleration, is necessary in order to be able to represent the changes on a micro-scale context [10]. These small scale scenarios are affected by traffic control and management strategies that are designed to change the modal events on a network, hence instantaneous speed and acceleration are influenced (8).…”
Section: Mobile Source Emission Modelsmentioning
confidence: 99%
“…However, the SCFs were developed using data collected with fixed driving cycles. Thus, this approach may not adequately capture the effects of driving and vehicle dynamics on fuel consumption and emissions, especially when assessing traffic management strategies [31]. CMEM [32] was developed at a microscopic level to predict secondby-second fuel consumption and emissions using operational activities of a vehicle.…”
Section: Eco-index Calculation Modulementioning
confidence: 99%
“…Studies have shown a corresponding relationship between the fuel consumption per unit distance and vehicle speed and acceleration [11,31,34]; however, speed or acceleration alone is inadequate for researching fuel consumption. Thus, there is a need is to discover another parameter associated with both the speed and acceleration to discuss the regularity of fuel consumption.…”
Section: Eco-index Calculation Modulementioning
confidence: 99%
“…In [Cappiello et al, 2002] und basiert auf der physikalischen Energie P , die ein Auto pro Zeiteinheit benötigt. Sie hängt von seinem Grundleistungsbedarf P 0 , seiner Momentanleistung F , sowie der Geschwindigkeit v ab.…”
Section: Verkehrssimulation Und Benzinverbrauchunclassified